(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Introduction: Head and neck swellings have a wide range of causes, appearances, and behaviours. Developing a diagnostic plan for their accurate management is crucial. This requires a thorough understanding. Therefore, this study aimed to describe the clinicopathological profile of various head and neck swellings in a tertiary care center. Materials and Methods: This prospective descriptive study was conducted on 190 patients at a tertiary care center in Northern India. After a detailed workup, clinical, USG and FNAC findings were documented and patients were managed medically or surgically. The findings were then correlated with the final HPE report. Results: Of the 190 patients, 139 (73.2%) had non-neoplastic swellings, 21 (11.1%) had benign neoplasms, and 30 (15.7%) had malignant lesions. Neck swellings accounted for 71.6% (n=136), with the majority being thyroid swellings (47.1%) and lymphadenopathy (26.4%). Head swellings comprised 28.4% (n=54), predominantly involving the parotid gland (25.9%) and post-traumatic nasal swellings (9.3%). The most common etiology was infective or inflammatory (55.2%). Conclusion: A systematic approach is essential for determining a preliminary diagnosis, considering potential alternative diagnoses, and devising an appropriate treatment plan for patients with palpable masses. Bangladesh J Otorhinolaryngology 2025; 31 (1) Page-16-27